Determinantes do desempenho competitivo da cotonicultura no município de Campo Verde – MT, no período de 2014 - Muniz, Meiresângela Miranda (2015)
The scenario of the cotton crop in Brazil has been gaining strength due to the fall in the economy of other cultures, for example, the coffee in 1929. In Mato Grosso this culture has replaced other crops (livestock and subsistence farming). Despite several changes in the economic, social and cultural scope, the cotton farming has strong predominance in the agricultural sector as a primary export. However, the cotton-producing region as a whole does not have a homogeneous development and much less an equal productivity. Among the cotton producing municipalities in the state, it was chosen Campo Verde because the representativeness of its production and present a diverse dynamics in its economic activity. Therefore, the research seeks the theoretical frameworks on competitiveness focusing on efficiency to try to answer the following questions: what are the determining factors for competitiveness in the cotton farming in the municipality of Campo Verde? And by dividing the number of producers investigated in three groups of competitive performance (high performance, intermediate performance and low performance), it is questioned: The proportion of producers with high competitive performance prevails over the other two? For this purpose, we used questionnaires applied in loco and secondary data, seeking to define the main variables corresponding to the proposed theme / question. Thus, we used the factor analysis method to measure and identify the key factors determining the competitiveness of the cotton farming in Campo Verde. As a result it obtained five factors that determine the competitiveness of the cotton farming of Campo Verde. And from the total universe surveyed, 40% of cotton farmers have achieved high competitive performance with competitive performance index (IDC) value above 70.